2021
DOI: 10.1177/0145561320986031
|View full text |Cite
|
Sign up to set email alerts
|

Chondromesenchymal Hamartoma With Nasopharyngeal Involvement: Two Unusual Cases of an Extremely Rare Lesion

Abstract: Chondromesenchymal hamartoma (CMH) is a rare, benign lesion of the nasal cavity, paranasal sinuses, and skull base, composed of islands of hyaline cartilage in a myxoid background. The vast majority of CMH cases are infants and young children. According to the world literature, nasopharyngeal involvement of CMH is extremely rare. In all cases, the lesions were masses protruding from the nasal cavity or paranasal sinuses to the nasopharynx. We hereby report 2 adult male patients with masses completely situated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Типичная локализация: перегородка и преддверие носа, решетчатый лабиринт, клиновидная и верхнечелюстная пазуха. Для данного образования характерны быстрый рост и значительная костная реконструкция, которая может имитировать злокачественный процесс [11,12]. Этиология возникновения окончательно не установлена.…”
Section: Discussionunclassified
“…Типичная локализация: перегородка и преддверие носа, решетчатый лабиринт, клиновидная и верхнечелюстная пазуха. Для данного образования характерны быстрый рост и значительная костная реконструкция, которая может имитировать злокачественный процесс [11,12]. Этиология возникновения окончательно не установлена.…”
Section: Discussionunclassified
“…Accordingly, nasal chondromesenchymal hamartoma should first be considered as a benign lesion composed of mesenchymal elements including smooth muscle, adipose, and cartilaginous tissue. 12 According to some authors, the term ''mucocutaneous angiomyolipoma'' should be ignored, as this tumor is actually an angioleiomyoma with adipocyte differentiation. 13 D'Aguanno et al 13 found that the presence of mature adipocytes in the tissue of an otherwise typical nasal angioleiomyoma is not a rare occurrence.…”
Section: Discussionmentioning
confidence: 99%